Gender differences in the prognostic impact of uric acid in patients with heart failure and preserved ejection fraction - Xuefeng Wu; Jianming Li; Zhaoyan Xu; Yingqing Feng (BMC Cardiovascular Disorders)
Abstract Background Uric acid has been identified as an independent predictor of poor outcomes in patients with heart failure with preserved ejection fraction (HFpEF). However, the impact of gender differences on this association is not fully explored. Methods This retrospective cohort study included hospitalized patients with HFpEF from June 2018 to October 2022. The primary outcome was a composite endpoint, defined as the occurrence of all-cause mortality and heart failure readmission. Kaplan–Meier survival analysis and stratified Cox regression examined the combined effect of gender and uric acid on the composite endpoint, and restricted cubic spline curves were applied to visualize the relationship. Results The study included 547 patients, with 267 females and 280 males. In the entire cohort, each mg/dL increase in uric acid was associated with a 4% increase in the risk of the composite endpoint (HR: 1.04, 95%CI:1.01–1.09). This association was more pronounced in females, with a 9% increase in the risk of the composite endpoint per mg/dL increase in uric acid (95%CI: 1.02–1.17). Restrict cubic spline curves analysis demonstrated a significant linear correlation between increasing uric acid levels and higher risk of the composite endpoint in female patients (P = 0.028). Kaplan–Meier analysis revealed higher survival probabilities for females compared to males (P = 0.002). However, survival rates for females with high uric acid levels were similar to those for males with high uric acid levels. Conclusions Baseline serum uric acid levels are significantly associated with the composite endpoint in patients with HFpEF, particularly among females.